Reference intervals for leukocyte cell population data in healthy adults in Zigong region, China - Jianhong Yu; Yu Chen; Haodong Hua (Scientific Reports)
Abstract Leukocyte cell population data (CPD), obtained through contemporary hematology analyzers, provide critical insights into the functional and morphological states of immune cells. However, clinically relevant reference intervals for these parameters remain scarce, particularly in region-specific populations. This study sought to establish age- and sex-specific reference intervals for CPD parameters in healthy adults residing in Zigong, China. A total of 7,274 individuals were selected after rigorous screening from 10,673 candidates undergoing routine health checkups. Blood samples were analyzed utilizing a Sysmex XN-1000 analyzer. Statistical methods were employed to assess data distribution, identify and exclude outliers, and generate reference intervals by CLSI EP28-A3C guidelines. Significant differences were observed between males and females across multiple CPD parameters, with age-related trends also being identified. Validation with an independent dataset confirmed that over 90% of results fell within the established reference intervals. These findings present the first localized reference standards for CPD parameters in Zigong, potentially enhancing diagnostic accuracy and supporting clinical decision-making in laboratory medicine.